What People Say About Halal Tourism? - Assyifa (Halal Tourism and Pilgrimage, 2021)
This study aims to analyze the sentiments generated from public opinion taken from Twitter and related to halal tourism. The method used was a qualitative approach with descriptive statistics from literature studies with halal tourism. The data analyzed consisted of 906 tweets during 2021. The results showed that neutral sentiment was the highest result with 97.2%, followed by positive sentiment at 2.2% and negative sentiment at 0.6%. The diversity of the results of this sentiment is obtained because of the cons against the development of halal tourism.